Seroprevalence and Risk Factors of Cysticercosis in Pig farm Workers and Artisan/traditional pig Breeders in the Municipality of Mara, state of Zulia, Venezuela - Rafael Villalobos Perozo; Rosita Cheng; Odelis Díaz; Jesús Estévez; Sharline Beauchamp; José Cava; Alfonso Nacaid; Gustavo Soto; Carlina Castellano; Lesbia Pérez (Universidad del Zulia,Facultad de Medicina,Departamento de Enfermedades Infecciosas y Tropicales, 2007)
Objectives: to determine the seroprevalence and the risk factors for cysticercosis in pig farm workers and traditional pig breeders living in the municipality of Mara in the state of Zulia. Methodology: Serum samples were studied from 59 individuals of both sexes (33 masculine and 26 feminine), with ages ranging from 1 to 60 years old, including 18 pig farm workers and 41 traditional pig breeders and their relatives, to determine IgG anticysticercus antibodies by means of the ELISA method, using Taenia crassiceps antigens, as well as an epidemiological survey. Results: The general seroprevalence was 15.25%. The group at greater risk was more than 40 years old. The consumption of crude or undercooked pig meat and performing activities related to pigs for prolonged periods were important risk factors. Discussion: The seroprevalence found in this population was high when compared with other papers that studied this type of population. The affected age group (40 years old) and the consumption of crude or undercooked pig meat agreed with the results obtained in other studies made in Venezuela and other countries. Performing frequent activities related to pigs was also was shown to be a risk factor. With a linear multiple regression model, it was demonstrated that the concurrence of these three factors increases the risk of positive serology. Conclusions: the high prevalence demonstrated in this population when compared with other populations previously studied suggests performing an epidemiological surveillance for cysticercosis.